Learning to Read and Memorize the Qur'an as the Media to Help Make Easier the Students in Studying Arabic at Al-Azhar Cairo Islamic School of Palembang Indonesia - Achmad Brian Athoillah (International Islamic Schools Alliance, 2020)
Al-Azhar Islamic school Cairo Palembang is one of the school's curriculum of Al-Azhar Cairo Egypt in the field of tahfidzul qur’an, Ulum Al-Syar'iyyah and the Arabic language. The third matter that is all based on the Arabic that is good and right in order to support the achievement of a taerget that has been set by the school. Learn Quran is the basic foundation which was almost unknown even felt by every muslim when still aged. Starting from pronouncing the letter per letter to understand it properly and correctly. Likewise in this school, also did not immediately leave the important teachings of already planted by the teachers who have been teaching him. Not a few pupils from this school who come from schools that barely taught again during the SD. As Christian schools or the like. It is clear to students the impact when they entered the Al-Azhar Islamic school Cairo. Starting from reading the Qur'an to other Islamic lessons. Especially the three material taken directly from Cairo Egypt writers already mentioned at the beginning. The impact is felt when taught their kids that are still far in the arab berbahsa pretty much felt by most faculty. And then learn the Qur'an was one of the influences for students who are native speakers. Why learn the Qur'an? Because according to save writers studying the Qur'an is the basic foundation then will be able to speak Arabic well. Or have more precision level. As time went on in this school have started there though has not been so significant target achievements but it is demonstrating that that learning the Qur'an also has an impact on pupils in understanding arab criticism. As for the influence that can be pursued in a way getting used, provide understanding, invites them to participate actively in the reading or studying the Qur'an.